The multilevel influence of supervisor helping behavior on employee voice behavior: A moderated mediation model - Fan, Peihua; Liu, Yuzhao; Liu, Haowen; Hou, Mingjun (Frontiers in Psychology, 2022)
Based on conservation of resource theory, this study adopts an experience sampling method to build a cross-hierarchical mode to investigate the internal mechanism between supervisor helping behavior and employee voice behavior. The empirical results from 76 employees’ dynamic data show that the supervisor helping behavior has no significant direct effect on the employee voice behavior; thriving at work plays a mediating role between supervisor helping behavior and employee voice behavior. Psychological availability, as a moderator, not only positively moderates the effect of supervisor helping behavior on thriving at work but also positively moderates the mediation of thriving at work on the relationship between supervisor helping behavior and employee voice behavior. From the dynamic perspective, this study adds to the literature on supervisor helping behavior and employee voice behavior, and it has practical implications on managerial decision-making.